Using context variety and students' discussions in recognizing statistical situations. (6th August 2015) - Silva, José Luis Ángel Rodríguez; Aguilar, Mario Sánchez
Summary: We present a proposal for helping students to cope with statistical word problems related to the classification of different cases of confidence intervals. The proposal promotes an environment where students can explicitly discuss the reasons underlying their classification of cases.